Pengaruh Substitusi Proporsi Limbah Kardus Dan Penambahan Nutrisi Air Leri Terhadap Produksi Jamur Tiram Putih (Pleurotus ostreatus) - Asep Saepudin; Darso Sugiono; Rommy Andhika Laksono (Jurnal Ilmiah Wahana Pendidikan, 2023)
Due to the difficulty in obtaining planting media and the limited availability of nutrients contained in the growing media, cardboard is an industrial waste that can be used as an alternative medium. Leri water fermentation should be added with nutrients in the oyster mushroom growing media. ) This study aims to obtain a combination of substitution of cardboard and nutrient media proportions that gives the highest yield of white oyster mushroom production. The research method used was an experimental method with a single factor Randomized Block Design (RBD). There were 10 treatment combinations, namely A (control), B (25% Cardboard + 20 ml Leri Water), C (25% Cardboard + 40 ml Leri Water), D (25% Cardboard + 60 ml Leri Water), E (Cardboard). 50%+Leri Water 20 ml), F (Cardboard 50%+Leri Water 40 ml), G (Cardboard 50%+Leri Water 60 ml), H (Cardboard 75%+Leri Water 20 ml), I (Cardboard 75% + 40 ml Leri Water) and J (75% Cardboard + 60 ml Leri Water). The results of the study using analysis of variance using the Least Significant Difference (BNT) test with a significance level of 5% showed that I (Cardboard Paper 75% + Leri Water 40 ml) gave the highest results on the parameters of the number of fruit clumps per baglog (2.28 pieces), the diameter of the hood fruit per baglog (15.01 cm), fresh weight of mushrooms per baglog (168.61 grams), and harvest intensity (1.28).